An Analysis of Code-mixing in Doctor-Patient Communication in Rasheed Shekoni Teaching Hospital Dutse, Jigawa State. - Jamilu Aminu; Adamu Alhaji Ibrahim; Buhari Habu; Sani Adamu (West African Journal of Interdisciplinary Research, 2026)
This study analyzes Code-mixing in Doctor-Patient Communication in Rasheed Shekoni teaching hospital Jigawa state. The objectives of the research are to identify the instances of code-mixing in Doctor-Patient communication, analyse the types of code-mixing in Doctor-Patient communication, examine the reasons for the use of code-mixing as well as investigate the linguistic effects of code-mixing in Doctor-Patient communication. The study employs a typology of code-mixing Theory for the data analysis and ethnography of communication method for the solicitation of data. The research finding shows that, Code-mixing in Rasheed Shekoni teaching hospital cuts across the three types comprising insertion, alternation as well as congruent lexicalization and, it is complex due to the application of some linguistic aspects involving lack of equivalence, abbreviation, show of identity, euphemism, calling attention, making explanation, expressing sympathy, borrowing, clipping, making prescription, coining a word, expressing solace, making appointment, emphasis as well as making referral. It furthermore proves that, the actual or intended meaning is sometimes not precisely communicated to the parties involved due to the unclearity / vagueness of the code-mixed lexical items.